Effect of soil-groundwater system on migration and transformation of organochlorine pesticides: A review - Haohao Li; Lin Huo; Rui Zhang; Xuefan Gu; Gang Chen; Ying Yuan; Wenbing Tan; Kunlong Hui; Yu Jiang (Ecotoxicology and Environmental Safety)
Soil is the place where human beings, plants, and animals depend on for their survival and the link between the various ecological layers. Groundwater is an important component of water resources and is one of the most important sources of water for irrigated agriculture, industry, mining and cities because of its stable quantity and quality. Soil and groundwater are important strategic resources highly valued by countries around the world. However, in recent years, the deterioration of the ecological environment of soil-groundwater caused by industrial, domestic, and agricultural pollution sources has continued to threaten human health and ecological security. Among them, organochlorine pesticides (OCPs), as typical organic pollutants, cause very serious pollution of soil and groundwater environment. However, most studies on the pollution of OCPs have focused on the aboveground or surface water environment, and little consideration has been given to the pollution and hazards of OCPs to the deep soil and groundwater environment, especially the effects of different environmental factors on the transport and transformation of OCPs in soil-groundwater. Moreover, in addition to the influence of a single factor on it, the interactions that arise between different factors cannot be ignored. This paper focuses on two major sources of OCPs in soil and groundwater environments, compiles and summarizes the effects of environmental factors such as pH, microbial communities and enzyme activities on the transport and transformation of OCPs in soil and groundwater systems, discusses the synergistic effects of individual environmental factors and others, and comprehensively analyses the effects of synergistic effects of various environmental factors on the transport and transformation of OCPs. In the context of ecological civilization construction, it provides the scientific basis and theoretical foundation for the prevention and treatment of OCPs-contaminated soil and groundwater, and puts forward new ideas and suggestions for the research and development of green, eco-friendly remediation and treatment technologies for OCPs-contaminated sites.